Synthesis of N3-Substituted Carboranyl Thymidine Bioconjugates and their Evaluation as Substrates of Recombinant Human Thymidine Kinase 1 - Agarwal, Hitesh K. (2012)
Four different libraries of overall twenty three N3-substituted thymidine (dThd) analogues, including eleven 3-carboranyl thymidine analogues (3CTAs), were synthesized. The latter are potential agents for Boron Neutron Capture Therapy (BNCT) of cancer. Linker between the dThd scaffold and the m-carborane cluster at the N3-position of the 3CTAs contained amidinyl-(3e and 3f), guanidyl-(7e-7g), tetrazolylmethyl-(9b1/2-9d1/2), or tetrazolyl groups (11b1/2-11d1/2) to improve human thymidine kinase 1 (hTK1) substrate characteristics and water solubilities compared with 1(st) generation 3CTAs, such as N5 and N5-2OH. The amidinyl- and guanidyl-type N3-substitued dThd analogues (3a-3f and 7a-7g) had hTK1 phosphorylation rates of <30% relative to that of dThd, the endogenous hTK1 substrate, whereas the tetrazolyl-type N3-substitued dThd analogues 9a, 9b1/2-9d1/2 and 11a, 11b1/2-11d1/2) had relative phosphorylation rates (rPRs) of >40%. Compounds 9a, 9b1/2-9d1/2 and 11a, 11b1/2-11d1/2 were subjected to in-depth enzyme kinetics studies and the obtained rk(cat)/K(m) (k(cat)/K(m) relative to that of dThd) ranged from 2.5-26%. The tetrazolyl-type N3-substitued dThd analogues 9b1/2 and 11d1/2 were the best substrates of hTK1 with rPRs of 52.4% and 42.5% and rk(cat)/K(m) values of 14.9% and 19.7% respectively. In comparison, the rPR and rk(cat)/K(m) values of N5-2OH in this specific study were 41.5% and 10.8%, respectively. Compounds 3e and 3f were >1,900 and >1,500 times, respectively, better soluble in PBS (pH 7.4) than N5-2OH whereas solubilities for 9b1/2-9d1/2 and 11b1/2-11d1/2 were only 1.3 – 13 times better.